Metal additive manufacturing for industrial applications - Afkhami, Shahriar; Amraei, Mohsen; Unt, Anna; Piili, Heidi; Björk, Timo (LUT University, 2021)
This report aims to have an overview to development actions of a knowledge-based know-how cluster of metal additive manufacturing (AM) in Finland's South Karelia region. This report aims also to investigate the needs of regional industries to become more aware and open towards using AM in their production lines. At first, a brief history of additive manufacturing introducing the preliminary concepts of metal AM, its generic principles and available processes are discussed. Next, the status of AM activities in Finland and other Nordic countries is discussed. Finally, it shares the results of a case study to get the reader more familiar with metal AM. The case study of this report shows that 3D printed metals such as stainless steel 316L have a strong potential to compete with their traditionally manufactured counterparts, even excel them regarding many specific material properties and applications. Tämän raportin tarkoituksena on läpikäydä Etelä-Karjalan metallien lisäävän valmistuksen (engl. additive manufacturing, AM) osaamiskeskittymän perustamiseen liittyviä näkökohtia. Tässä katsastettu alueellisen teollisuuden tarpeita, jotta lisäävän valmistuksen käyttöönottoa voitaisiin laajentaa paremman tietopohjan kautta. Aluksi tässä raportissa käsitellään lyhyesti metallien lisäävän valmistuksen historiaa, ja esitellään tekniikan keskeisimmät käsitteet, sen yleiset periaatteet ja käytettävissä olevat prosessit. AM-toiminnan tilasta Suomessa ja muissa Pohjoismaissa esitellään myös yhteenveto. Lopuksi raportissa käydään case studien tuloksia läpi, jotta metallien lisäävän valmistuksen käytännön sovelluksia ja niiden mahdollisuuksia voidaan ymmärtää paremmin. Nämä esimerkit osoittavat selkeästi sen, että metallien (kuten 316L) 3D-tulostuksella, on suuri mahdollisuus olla teollisesti varteenotettava valmistustekniikka. Useimmat tulostettujen kappaleiden ominaisuudet ovat samat kuin perinteisestikin valmisteluilla, ja joissain tapaukissa jopa paremmat. Publishers version